Proceedings of the 2005 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.2005.1570120
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High Fidelity Haptic Device for Telesurgery

Abstract: Good performances in tele-surgery procedures is achieved when the surgeon acts and feels as if he were holding directly in his hands the surgical instruments interacting with the patient. To reach this goal, a high fidelity haptic device was recently developed at CEA LIST. As the development of such an input device calls for a precise understanding of the application requirements, we first introduce in this paper Minimally Invasive Surgery problematics and associated design guidelines. Then we focus on dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Cable capstan drives are also widely used on master-slave systems and haptic interfaces [16,[20][21][22][23][24]. They are composed of a first small input pulley attached to the motor axis, a cable wound on this pulley, and attached at both ends to a second larger output pulley fixed on the driven link.…”
Section: Highly Backdrivable Actuatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cable capstan drives are also widely used on master-slave systems and haptic interfaces [16,[20][21][22][23][24]. They are composed of a first small input pulley attached to the motor axis, a cable wound on this pulley, and attached at both ends to a second larger output pulley fixed on the driven link.…”
Section: Highly Backdrivable Actuatorsmentioning
confidence: 99%
“…In practice, the left hand robot is a reconditioned version of a master arm previously designed for abdominal telesurgery, and the right hand robot is a new haptic interface with a higher force capacity and stiffness specifically developed for this platform. Further details on these robots can be found in [23,24]. during these developments have shown that the most critical steps of this surgery require bi-manual movements in the Cartesian space with a maximum amplitude at the level of the surgery tool handle of about 162 to 194 mm in translation and 137° in orientation.…”
Section: Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The CEA LIST has recently developed a 6 DOF high fidelity haptic device for telesurgery (Gosselin et al, 2005). As serial robots are quite complex to actuate while fully parallel robots exhibit a limited workspace, this device makes use of a redundant hybrid architecture composed of two 3 DOF branches connected via a platform supporting a motorized handle, having thus a total of 7 motors.…”
Section: Presentation and Modelingmentioning
confidence: 99%
“…A large amount of literature was reviewed during the development of the previously mentioned mechanism [9][10][11][12][13][14], on the basis of which it has been established that a cable drive is the most commonly used driving system in haptic devices, due to practically zero backlash, stiffness, and backdrivability. The cable drive was, therefore, chosen as the driving system for our haptic robot, due to its many advantages.…”
Section: Introductionmentioning
confidence: 99%